The statistics of electric field fluctuations in liquid water - Reischl, Bernhard; Kofinger, J.; Dellago, C. (Taylor & Francis, 2009)
Electric field fluctuations play a major role in dissociation reactions in liquid water and determine its vibrational spectroscopic response. Here, we study the statistics of electric fields in liquid water using molecular dynamics computer simulations with particular focus on the strong but rare fields that drive dissociation. Our simulations indicate that the important contributions to the electric field acting on OH bonds stem from water molecules less than 7 away. Long-ranged contributions play a minor role.